Analysis of Alternative Strategies for Domestic Wastewater Systems Management and Development in Regency/City Governments (Case Study: South Tangerang City, Banten Province) - Nur Dewisri Fatihawati; Marisa Handajani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The impact of high urban population growth and increased development activities in various sectors has caused various problems in urban areas, one of which is waste water pollution. Through the “Wastewater System Management and Development Program”, the planning activity program must be able to improve the management and development of the domestic wastewater system. In addition, the implementation of the planning activity program must be in accordance with the conditions, especially in South Tangerang City, including the Planning for the Development of Domestic Wastewater (Grey Water) & Stool (Black Water) Management, Sludge Treatment Plant (IPLT), Scheduled Sludge Service Management (LLTT). and Preparation of Regional Regulations on Domestic Wastewater Management and Service Charges. The stages of this research include data collection, analysis of instrument validity and reliability, IFAS and EFAS analysis, SWOT and QSPM analysis. Some of the main planning activity programs, based on literature studies and interviews with city government stakeholders in improving the management and development of domestic wastewater systems in South Tangerang City include Planning for the Development of Domestic Wastewater & Stool Management Systems, Planning for Development of Sludge Treatment Plants owned by the South Tangerang City Government.